Impact of Technology Introduction on Shallot Farming Performance in Central Java - Mariyono, Joko; Setiadi, Agus; Santoso, Siswanto Imam; Horne, Paul; Afari-Sefa, Victor (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Technological improvement, particularly to prevent yield loss, will benefits shallot farmers. Technology packages related to crop protection have been introduced to shallot farmers in three shallot-producing areas namely Brebes, Tegal and Pemalang, Central Java. This study aimed to analyze the effect of technology package introduction on the performance of shallot farming. The analysis is carried out using a difference-in-difference approach which ensures the real impact of the technology. The fundamental analysis is economic threshold theory. A total of 160 samples consisting of 112 adopters and 48 non-adopters in this study were spread over three regions. A simple paired and independent t-tests were applied to the hypotheses. Agricultural performance indicators include productivity, costs of production and net income. The results showed that the performance of shallot farming increased significantly due to technological improvements. The technology packages have been able to increase productivity, reduce costs of production and enhance net income of shallot farming. This result is very important because the reduction of pesticides can improve environmental quality and health